ANALISIS KETERAMPILAN MENGAJAR DALAM PRAKTIK PEMBELAJARAN MAHASISWA PENDIDIKAN BAHASA ARAB PADA MATA KULIAH MICROTEACHING - Ahmad Baidhowi (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2026)
Microteaching is a learning model designed to train the pedagogical competence of prospective teacher students through limited-scale teaching practice. This study aims to analyze the teaching skills of PBA students at Muhammadiyah University of Tangerang. The results of the analysis are expected to be an evaluation for lectures in monitoring and providing input to prospective teacher students, as well as for students to improve their competencies. This study was conducted using a quantitative approach with a descriptive design. The instruments in this study were lecturer observation sheets and a learning assessment rubric criterion, then converted into qualitative data through a score range percentage table. This study found that the overall skills of prospective teacher students in the Arabic Language Education Study Program, class of 2024, obtained an average score of 79,73%, which is categorized as good. In detail, the score obtained for opening skills was 80,11% (good). Explanation skills were 86,47% (very good). Variation skills were 82.26% (good). Reinforcement skills obtained a score of 81,11% (good). Questioning skills obtained a score of 79,32% (good). Classroom management skills scored 74,79% (adequate). Discussion guidance skills scored 76,84% (good). Small group and individual teaching skills scored 77,68% (good). Closing skills scored 78,95% (good). Based on the percentage results above, it can be seen that there is one basic teaching assessment indicator that still needs to be evaluated and improved, namely classroom management skills.